Clustering stationary and non-stationary time series based on autocorrelation distance of hierarchical and k-means algorithms - Mohammad Alfan Alfian Riyadi; Dian Sukma Pratiwi; Aldho Riski Irawan; Kartika Fithriasari (International Journal of Advances in Intelligent Informatics, 2017)
Observing large dimension time series could be time-consuming. One identification and classification approach is a time series clustering. This study aimed to compare the accuracy of two algorithms, hierarchical cluster and K-Means cluster, using ACF’s distance for clustering stationary and non-stationary time series data. This research uses both simulation and real datasets. The simulation generates 7 stationary data models and another 7 of non-stationary data models. On the other hands, the real dataset is the daily temperature data in 34 cities in Indonesia. As a result, K-Means algorithm has the highest accuracy for both data models.